A prospective multicentre study of per‐oral endoscopic myotomy (POEM) for achalasia in Australia. Issue 4 (21st February 2021) - Gupta, Sunil; Sidhu, Mayenaaz; Banh, Xuan; Bradbear, Joseph; Byth, Karen; Hourigan, Luke F; Raftopoulos, Spiro; Bourke, Michael J
Abstract: Objective: To describe the clinical and procedural outcomes of per‐oral endoscopic myotomy (POEM) for achalasia in Australia. Design, setting: Prospective observational study in three Australian tertiary referral centres, 5 May 2014 – 27 October 2019 (66 months). Participants: Patients who had undergone POEM for achalasia. Major outcome measures: Eckardt scores calculated prior to POEM and six months, one year, and two years after POEM. The primary outcome was clinical success, defined as an Eckardt score of 3 or less without a second intervention. Results: 142 patients underwent POEM for achalasia; their mean age was 52 years (SD, 18 years), 83 were men (58%), and the median length of hospital stay two days (IQR, 1–3 days). Their mean Eckardt score before POEM was 8.0 (SD, 2.4) and 1.1 (SD, 1.6) six months after POEM; it did not change significantly between six months and two years after POEM (mean monthly increase, 0.014 points; 95% CI, –0.001 to 0.029). A total of 127 patients (89%) improved clinically after POEM. Intra‐procedural capnoperitoneum was the only risk factor associated with treatment failure (adjusted hazard ratio, 2.85; 95% CI, 1.08–7.51). Previous treatments — botulinum toxin injection (25 patients, 18%), endoscopic balloon dilatation (69, 49%), and Heller myotomy (14, 10%) — did not affect POEM outcomes. Five patients (4%) experienced major adverse events, including pneumonia, oesophageal leak, empyema and melaena, that were managed during admission and without sequelae. Conclusions: POEM is an effective treatment for achalasia. Significant reductions in Eckardt scores achieved by six months are sustained at two years. POEM can be both a first line definitive therapy and a salvage therapy for patients not helped by other treatments.